2005
DOI: 10.1095/biolreprod.104.038539
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophils in Matrix Metalloproteinase Activity in the Preimplantation Mouse Uterus1

Abstract: Matrix metalloproteinases (MMPs) have been implicated in embryonal implantation processes such as trophoblast invasion and decidualization. The temporal and spatial distributions of MMP bioactivities were analyzed by in situ zymography, which indicated these activities to be markedly increased in the postcoital mouse uterus compared with those in the later implantation stage. Activity was ascribed to proMMP9, which moved from the uterine serosa to the endometrium but was not associated with mRNA up-regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
1
16
0
2
Order By: Relevance
“…In our experiments, we detected only the latent form of MMP-9 (pro MMP-9) in the gelatin zymography. Regarding MMP-9, it has been reported that MMP-9 is not always detected in many tissues in vivo, although pro MMP-9 is converted to MMP-9 by various protease such as MMP-1, MMP-2, MMP-3 or plasminogen activator in vitro [54]. In addition, MMP-9 activation locally occurs in a pericellular environment by inflammatory response, leaving much of the secreted MMP in its pro-form [55].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we detected only the latent form of MMP-9 (pro MMP-9) in the gelatin zymography. Regarding MMP-9, it has been reported that MMP-9 is not always detected in many tissues in vivo, although pro MMP-9 is converted to MMP-9 by various protease such as MMP-1, MMP-2, MMP-3 or plasminogen activator in vitro [54]. In addition, MMP-9 activation locally occurs in a pericellular environment by inflammatory response, leaving much of the secreted MMP in its pro-form [55].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have been identified as the key source of MMP-9, a collagen specific protease during the peri-implantation period [93], while macrophages are known to produce a range of MMPs. A comprehensive study by Chow et al [94] in the golden hamster showed that expression of molecules involved in ECM remodelling are controlled in a temporal and spatial manner and that seminal plasma is implicated in their regulation.…”
Section: Tissue Remodelling and Seminal Plasmamentioning
confidence: 99%
“…In addition to serine proteases, other proteases like MMPs are also capable of degrading extracellular matrix proteins. Although MMP proteins do not possess the catalytic triads required for proteolytic function in KLKs (His57, Asp102, and Ser195) [42], neutrophils bearing proMMP9 can be attracted by seminal plasma and their activities are elevated post-coitus in the female uterus [43]. In our model, all Mmp transcripts and their inhibitors were expressed at the same level between Esr1 f/f and Wnt7a Cre/+ ; Esr1 f/f uteri.…”
Section: Discussionmentioning
confidence: 99%